PENOLAKAN KOMUNITAS LOKAL NAGARI PADANG TAROK TERHADAP KEDATANGAN TRANSMIGRAN SUKU ANAK DALAM - Indeska Putra; Indraddin Indraddin; Alfan Miko (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
This research discusses the rejection of Anak Dalam Ethnic transmigrants in Padang Tarok Village, Kamang Baru District, Sijunjung Regency. The purpose of this study is to explain and describe the reasons for the local community of Padang Tarok Village to reject the Anak Dalam Ethnic Transmigrant and to analyze it using the Social Exclusion by Rene Lenoir. This research uses a qualitative approach. The selection of informants was carried out by purposive sampling. Data collection was carried out using involved observation, in-depth interviews, and documentation. The result of the study shows that the rejection of Anak Dalam Ethnic transmigrants occurs because of differences in religious and cultural values between the Anak Dalam Ethnic and the local community of Padang Tarok Village. Due to differences in religious and cultural values between the Anak Dalam Ethnic and the local community, the transmigration program for the Anak Dalam Ethnic was not implemented according to the plan